Symposium 3: Culture and eLearning Design – Reflections on Integrating F2F and Online - Brewster, Eric; Cavaleri, Nicola; King, Anny; Zähner, Christoph (Proceedings of the International Conference on Networked Learning, 2006)
The CUTE (Chinese University Teachers Training in English) pilot project (2003-2004) within the framework of the eChina UK programme aimed at improving the linguistic, presentation, and writing skills for academic exchange and teaching of Chinese academics across several fields at Tsinghua University, Beijing. One of the key features of this programme from the start was the specification of a 70% online to 30% F2F delivery of the course. During the development, trialling and implementation of the programme, significant insights into the culture of the Chinese classroom and the parameters for effective online design were gained. These insights ranged from insights into the nature of Chinese learning strategies, attitudes towards roles of teachers and learners, to attitudes towards the use of online materials. This paper will focus on the results of the action research carried out during the design and implementation of the online support materials (December 2003-September 2004) and the F2F teaching experience (July and September 2004). A combination of observations, testing, questionnaires, individual and focus group interviews, tracking data, and comments in diaries and on the online forum inform the reflections presented in this paper. The needs analysis, 12 week course (three weeks F2F contact and 9 weeks of supported online self-study), and the continuous, collaborative development of the online course materials were the first contact points with Chinese classrooms for the tutors and provided numerous challenges for tutors, trainees, designers, and content developers to established practices and significant opportunities for self-development, critical reflection, and insights into learning and teaching in a F2F/online integrated course.